Pain catastrophizing and pain-related emotions: influence of age and type of pain - Ruscheweyh, Ruth; Nees, Frauke; Marziniak, Martin; Evers, Stefan; Flor, Herta; Knecht, Stefan (The clinical journal of pain, 2011)
Objectives - One of the most important determinants of the individual pain experience is pain catastrophizing, reflecting an excessively negative cognitive and emotional orientation toward pain. Its assessment by standard questionnaires, which ask participants to reflect on idiosyncratic past painful experiences, is important. It is currently not known whether different types of pain differently shape pain catastrophizing. Furthermore, as the regulation of emotions changes during the life span, age may affect pain catastrophizing, as well. - Methods - In this study, 134 healthy participants, differentiated into 2 age groups (20 to 40 y and 50 to 70 y), completed the Pain Catastrophizing Scale with reference to their past experiences with 3 common types of day-to-day pain (headache, back pain, dental pain). - Results - On average, the different types of pain shared one-third of the variance in pain catastrophizing. Pain-type-specific catastrophizing scores were more strongly related to ratings of sensory and emotional pain characteristics than standard catastrophizing scores. In younger adults, pain catastrophizing was preferentially associated with emotional responses to pain whereas in older adults, it was preferentially associated with pain intensity ratings. - Discussion - This study indicates that for day-to-day pain, catastrophizing significantly depends on pain type. The results suggest the use of pain-type-specific instructions for catastrophizing questionnaires because it may lead to better prediction of clinically relevant pain characteristics, such as pain intensity. Furthermore, pain catastrophizing seems to change during the life span, with a higher engagement of emotional versus sensory pain processing in younger compared with older adults.
Gesehen am 22.09.2022